THE ANALYSIS OF MEASUREMENTS FOR SMALL AND MEDIUM BUSINESSES SUPPORT - E. A. Tabolova; M. A. Gatagonova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Market transformations in economic system of the Russian Federation from 1991 conditioned the change of consumers drug support organization principles, and the market formation led to the business development in this field. Pharmaceutical market is a socially significant market, which leads to the necessity of active realization of competitive business environment development in the conditions of effective state regulation and support. The problem of creation and development of small businesses has a special value for the national economy. These businesses provide the production of significant, and in some cases dominating part of a gross domestic product in many developed countries. State policy of small business support in Russia has become an individual system direction of social and economical state policy. It is formed by the principle of favorable conditions creation for small business development, especially in the fields of activity which give maximum social and economical effect. The actions coordination of federal executive authorities, executive authorities of federal subjects of the Russian Federation and local governments, social organizations, and entrepreneurs associations was enhanced to create the conditions of effective development of small business, form a flexible system of its state support. Analysis of the measurements implemented in the Republic of North Ossetia - Alania, aimed to the small business support for the evaluation of possibility of their use for pharmacy organization opening was the purpose of the study.